APRENDIZAJE COLABORATIVO Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES DE EDUCACIÓN BÁSICA - GUILCAPI QUINLLIN JOHANNA LIZETH (2024)
The research project focused on analyzing the impact of collaborative learning on the academic performance of third-year basic education students at the San José de Babahoyo School. Determining in one way or another that the implementation of this methodology faces challenges due to the lack of effective structures for group work and limited guidance from teachers, which has led to variable results in the academic performance of students. The general objective is to determine how collaborative learning impacts the academic performance of these students, while the methodology used is mixed, combining qualitative and quantitative approaches. Surveys, interviews and observation sheets were used that favored the analysis of academic data, involving the participation of teachers, students and the educational community. The importance of following ethical standards when working with children is highlighted, guaranteeing consent and confidentiality. This comprehensive approach seeks to thoroughly understand the situation of collaborative learning in the aforementioned school and its impact on academic performance, in order to propose recommendations to improve this educational process and thus improve the academic performance of the students of said educational institution.